Living Islamic history: studies in honour of Professor Carole Hillenbrand - Suleiman, Yasir; Hillenbrand, Carole (Edinburgh University Press, 2010)
This book gathers original research from a range of leading international scholars from the UK, Europe and the USA, throwing new light on a set of topics in medieval Islamic history, Islamic doctrine and practice, and the interaction between Islam and the modern world.